Carcharhinus albimarginatus ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Carcharhinus albimarginatus (Rüppell, 1837). Silvertip Shark. 3 m (9.8 ft) TL (Compagno et al. in Fischer et al. 1995). Indo-Pacific; western Pacific Ocean north to Ryuku Islands (Yoshino and Aonuma in Nakabo 2002); Patchily distributed from Bahía Magdalena, southern Baja California (Galván-Magaña et al. 2000) to Ecuador (Béarez 1996), including Guatamala, Colombia, Islas Revillagigedo, Clipperton Islands, Isla Cocos, and Islas Galápagos (Ebert et al. 2013). Depth: surface to 800 m (2,624 ft) or more (Compagno et al. in Fischer et al. 1995). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 17, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...